Social Environment Simulation in VR Elicits a Distinct Reaction in Subjects with Different Levels of Anxiety and Somatoform Dissociation - Kerous, Bojan; Barteček, Richard; Roman, Robert; Sojka, Petr; Bečev, Ondřej; Liarokapis, Fotis (International journal of human-computer interaction, 2020)
Virtual reality has taken many great strides in the recent years. It is increasingly used and is an accepted means of delivering behavioral therapy for phobias and anxiety disorders. In this paper, we examine methods of virtual reality stress induction for use in treatment of somatoform and anxiety disorders, as well as the adequate measures of the evoked stress response. In total, 42 healthy subjects took part in testing as part of this study. The results show that electrodermal activity is more sensitive in capturing a subject reaction to non-interactive social environment simulation while cardiovascular parameters better reflect task-related stress. Furthermore, our results suggest a distinct relationship between electrodermal activity and anxiety and cardiovascular parameters and somatoform dissociation. These results can point to a possibility of virtual reality utilization in the research and treatment of disorders in which anxiety and somatization are important features.